The Effectiveness of Sexual Education for Adolescents as a Prevention of STIs: Literature Review - Merida Simanjuntak (Sean Institute, 2023)
Sexual education in adolescents is an important and interesting topic to explore. Prevention of sexually transmitted infections in adolescents is one of the priorities of health measures. This study is to find out how effective sexual education in adolescents is to prevent sexually transmitted infections. Result: a large amount of scientific evidence that related to the subject was identified. Effectiveness in sexual education for adolescents support by the combination of actions and techniques, the implementation of digital technology and social media. Conclusion: Sexual education in adolescents is more effective when supported by appropriate methods and with the use of digital technology and accurate repetition of information.